Performance-Based Assessment on Esp Learning: A Preliminary Research - Anjar Setiawan; Rudi Hartono; Suwandi Suwandi; Sri Wuli Fitriati (International Conference on Science, Education, and Technology, 2021)
Performance-based assessment means as the process of acquiring, applying knowledge and skills through a learning process to enhance the ability of students in learning progress. Therefore, the present study is conducted to investigate the preliminary research of performance-based assessment on English for Specific Purposes (ESP) learning, particularly in writing and speaking skills. Further, this study implements descriptive qualitative method to analyzing, to describe, and to summarize various data collected from observation, interviews, questionnaire, and pre-test to non-English students at Universitas Muhammadiyah Semarang. The findings show that the students never implement performance-based assessment. The results of interview and observation indicate the students are excited to have a performance-based learning to enhance their English skills. Meanwhile, the results of questionnaire show the students’ enthusiastic to create learning products of writing and speaking. After given a pre-test of writing and speaking, the students’ average score is 68. In conclusion, the students need to have better learning activities by implementing performance-based assessment in English learning.